HUBUNGAN PENGETAHUAN, SIKAP DAN PERILAKU PENGAWAS MINUM OBAT (PMO) TERHADAP KEJADIAN TUBERKULOSIS (TBC) BERULANG DI KABUPATEN MUARA ENIM - Marini Marini; Indah Margarethy; Nungki Hapsari Suryaningtyas (SPIRAKEL, 2021)
The discovery of repeated TB cases is a problem in TB control in Muara Enim Regency. One of the causes of failure and lack of discipline of TB patients in taking medication is influenced by the role of the drug taking supervisor (PMO). The role of PMO is very important in monitoring, reminding and ensuring regularity of treatment for TB patients in order to achieve optimal treatment results. This study aims to examine the relationship between the role of the family as a supervisor for taking medication on the incidence of recurrent tuberculosis in Muara Enim district. This study used a case-control design with a retrospective approach. The research subjects were PMO in patients with recurrent TB/MDR TB as a case group and PMO in former TB patients who recovered on schedule as a control group. The comparison of case samples (46 samples) and controls (92 samples) was one to two (1:2). Data on the level of knowledge, attitude and behavior variables were assessed using a scoring system. The analysis uses the chi square test to get the odds ratio (OR) value. The results of the analysis show that the level of PMO knowledge is still below the program's expectations. The level of knowledge, attitudes and behavior of PMO are not related to the occurrence of recurrent TB cases. To increase the role of PMO, health workers can conduct counseling by changing the extension technique using more varied and communicative extension media.